Analisis Pengendalian Kualitas Produk dengan Menggunakan Metode Statistical Quality Control untuk Meminimumkan Jumlah Produk Cacat - Ahmad Julianda; Tasya Aspiranti; Umari Abdurrahim Abi Anwar (Bandung Conference Series: Business and Management, 2024)
Abstract. Elzone Sportindo is a clothing industry engaged in convection. Its production activities in Elzone Sportindo have been supervised but are still supervised by the owner himself, so it is still not effective and there are still products that are sold in a condition that is still not good for sale on the market. The purpose of this study is to find out how quality control is carried out by the Elzone Sportindo Convection Company, as well as its analysis using the method statistical quality control (SQC). The research method used is descriptive quantitative with data collection techniques namely observation, interviews, and documentation. The stages of data analysis using the SQC method begin with makingcheck sheet, histogram, scatter chart, pareto chart, control chart Np, and fishbone Chart. The results showed that there were four types of defective product defects in the Elzone Sportindo convection company, namely weak stitches, untidy stitches, size defects, and screen printing defects.Fishbone chart shows the cause of disability is from human factors, methods, machines, materials and media (environment).Pareto chart shows that the type of product damage is more dominant in screen printing defects by 41%. Actions that need to be taken to reduce defective products are making and implementing Standard Operating Procedures (SOP), conducting workforce training, using machines that use hot temperatures, and providing a comfortable place for workers so they can comfortably carry out their duties. Abstrak. Elzone Sportindo merupakan industri baju yang bergerak di bidang konveksi kegiatan produksinya yang ada di Elzone Sportindo sudah adanya pengawasan tetapi masih diawas oleh ownernya sendiri jadi masih belum efektif dan masih ada juga produk yang terjual dalam keadaan yang masih kurang baik untuk di jual dipasa. Tujuan dari penelitian ini untuk mengetahui bagaimana pengendalian kualitas yang dilakukan Perusahaan Konveksi Elzone Sportindo, serta analisisnya menggunakan metode statistical quality control (SQC). Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan teknik pengumpulan data yakni observasi, wawancara, dan dokumentasi. Tahapan analisis data menggunakan metode SQC dimulai dengan membuat check sheet, histogram, scatter chart, pareto chart, control chart Np, dan fishbone Chart. Hasil penelitian menunjukkan terdapat empat jenis cacat produk cacat yang ada di prusahaan konveksi Elzone Sportindo yakni cacat jahitan tidak kuat, cacat jahitan tidak rapih, cacat ukuran, dan cacat sablon. Fishbone chart menunjukkan penyebab kecacatan adalah dari faktor manusia, metode, mesin, material dan media (lingkungan). Pareto chart memperlihatkan jenis kerusakan produk lebih dominan pada cacat sablon sebesar 41%. Tindakan yang perlu dilakukan untuk mengurangi produk cacat yaitu membuat dan menerapkan Standar Operasional Prosedur (SOP), melakukan pelatihan tenaga kerja, menggunakan mesin yang menggunakan tempratur panas, dan memberikan tempat yang nyaman kepada pekerja agar bisa dengan nyaman melakukan tugasnya.